Accumulated fatigue affects running biomechanics depending on the performance level during a triathlon competition - Cala, A.; Navarro, E. (ISBS - Conference Proceedings Archive (Konstanz), 2009)
The purposes of the present study were 1) to examine the different responses to the accumulated fatigue between international and national level triathletes in competition, and 2) to compare the profile of the running part presented by the two different performance levels. 32 participants at Madrid 2008 Triathlon World Cup and 32 participants at Spanish National Championships 2008, made up the sample. We found higher values.